Eye Diseases Classification using Back Propagation with Welch Estimation based-Learning Rate - Shrooq; Hanaa M. Ahmed (Al-Qadisiyah Journal of Pure Science, 2021)
Human eye disease classification adapted by many pieces of research in the last decade due to the importance of eye organ for humans and the evolution in classification techniques. External eye diseases classified in this paper using backpropagation with non-linear cyclic learning rate based on welch estimation as a step for improving the performance of backpropagation. As a result, Classification accuracy achieved in this paper is (93.22%).